Spirituality in the writings of Etty Hillesum : proceedings of the Etty Hillesum Conference at Ghent University, November 2008 - Hillesum, Etty, 1914-1943.; Smelik, K. A. D., 1950-; Brandt, Ria van den, 1960-; Coetsier, Meins G. S. (Supplements to The Journal of Jewish Thought and Philosophy, 2010)
Much of the previous scholarship on Etty Hillesum (1914-1943) was done by individual scholars within the analyses of their fields. After the proceedings of the international Etty Hillesum Congress at Ghent University in November 2008, this Congress volume is the first joined effort by more than twenty Hillesum experts worldwide. It is an absorbing account of international scholarship on the life, works, and vision of the Dutch Jewish writer Etty Hillesum, whose life was shaped by the totalitarian Nazi regime. Hillesum's diaries and letters illustrate her heroic struggle to come to terms with her personal life in the context of World War II. Building on new interest in theology, philosophy, and psychology, this book revives Hillesum research with a comprehensive rereading of both her published works and lesser-known secondary discourses on her life. The result is fascinating. With the current explosion of interest in inter-religious dialogue, peace studies, Judaism, the holocaust, gender studies, and mysticism, it is clear that this Congress volume will be invaluable to students and scholars in various disciplines.